2022
DOI: 10.1186/s12884-022-04598-y
|View full text |Cite
|
Sign up to set email alerts
|

Immersive virtual reality on childbirth experience for women: a randomized controlled trial

Abstract: Objective To evaluate the effectiveness of immersive virtual reality (VR) on patient satisfaction as a distractive tool and pain relief among laboring women. Methods This was a randomized, controlled clinical trial with 42 laboring women allocated to VR intervention and control groups. Among women in the VR group, patient satisfaction with the use of VR was assessed by a Virtual Reality Satisfaction Survey, measured by a Visual Analog Scale (VAS) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…In this study, it was found that all pregnant women in the intervention group with PBT stated satisfaction with watching videos with VR headset, and almost all wished to use VR again during their next pregnancies and recommend the VR application for other pregnant women. In previous studies performed with pregnant women, it was also detected that almost all participants enjoyed watching nature images with VR headset during childbirth, and the vast majority wished to use VR again in the next deliveries (Carus et al, 2022; Cowles et al, 2019; Frey et al, 2019). The findings in our study investigating pregnant women are compatible with those in previous studies investigating the satisfaction level of the VR application experienced by the women during delivery.…”
Section: Discussionmentioning
confidence: 91%
“…In this study, it was found that all pregnant women in the intervention group with PBT stated satisfaction with watching videos with VR headset, and almost all wished to use VR again during their next pregnancies and recommend the VR application for other pregnant women. In previous studies performed with pregnant women, it was also detected that almost all participants enjoyed watching nature images with VR headset during childbirth, and the vast majority wished to use VR again in the next deliveries (Carus et al, 2022; Cowles et al, 2019; Frey et al, 2019). The findings in our study investigating pregnant women are compatible with those in previous studies investigating the satisfaction level of the VR application experienced by the women during delivery.…”
Section: Discussionmentioning
confidence: 91%
“…29 A further study revealed that using immersive VR during early labour not only improved patients' pain score but was also associated with a higher patient satisfaction with the overall childbirth experience. 35 A recent study described that the use of FaceTime to connect mothers and babies after childbirth may have a positive effect on mother-infant bonding but further research is needed assessing a wider range of outcomes. 36…”
Section: Open Accessmentioning
confidence: 99%
“…Another study showed that projecting echographic images of the baby obtained during pregnancy to the mother in labour via a VR headset was associated with a significant decrease of pain and anxiety symptoms 29. A further study revealed that using immersive VR during early labour not only improved patients’ pain score but was also associated with a higher patient satisfaction with the overall childbirth experience 35. A recent study described that the use of FaceTime to connect mothers and babies after childbirth may have a positive effect on mother–infant bonding but further research is needed assessing a wider range of outcomes 36…”
Section: Introductionmentioning
confidence: 97%
“…The pain-reducing effect of the immersive virtual environment is so significant that VR can be an effective therapeutic support in burn wound care [ 28 ] and during exercises to increase the range of motion in burned joints [ 29 ]. The specific properties of immersive virtual reality are also used to alleviate pain when undertaking various medical procedures in children and pediatric rehabilitation [ 30 ] and even in women during childbirth [ 31 ].…”
Section: Introductionmentioning
confidence: 99%